(untitled) (East West Medical College Journal, 2025)
Background: Hemodialysis is one of the main treatment procedure for the patients with end-stage of renal disease. Dialysis patients may encounter numerous physiological and psychological side effects from associated treatments, which may alter their lifestyle. Objectives: The aim of the study is to evaluate the quality of life in chronic kidney disease CKD patients undergoing hemodialysis and determined factors affecting the quality of life. Methods: A descriptive cross-sectional study was conducted among 102 hemodialysis patient from Kurmitola General Hospital October 2023 to September 2024, Dhaka by using convenient sampling technique. Data was collected by using two self-administered questionnaires; including socio-demographic questionnaire and the Health-Related Quality of Life scale (HRQOL-BRRIF) through face to face interview, the data was analyzed by using descriptive and inferential statistics. Results: Out of 102 hemodialysis patients their mean age was 54.00±9.833 years. Among them 68 (66.7%) are men and 74 (33.3%) are women. Overall, 62(60.8%) patients had poor quality of life and 40 (39.2%) reported good quality of life. This study revealed that various demographic factors are significantly associated with the quality of life among the patients undergoing dialysis. Conclusion: This study demonstrated a high prevalence of low quality of life among hemodialysis patients. Present study highlights several factors that healthcare policymakers and clinicians should consider to improve the quality of life of patients receiving hemodialysis. EWMCJ Vol. 13, No. 2, July 2025: 109-11